IMF Staff Papers, Volume 48, No. 2. (IMF Staff Papers; IMF Staff Papers ;, 2001)
This paper analyzes the link between product variety and economic growth. It finds support for the hypothesis that a greater degree of product variety relative to the United States helps to explain relative per capita GDP levels. The paper presents an empirical study for South Africa, which indicates that there exists a stable money demand type of relationship among domestic prices, broad money, real income, and interest rates, as well as a long-term relationship among domestic prices, foreign prices, and the nominal exchange rate.